Representações do humor político na revista Fradim sobre a ditadura militar (1976-1978): o ensino de história através dos quadrinhos de Henfil - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2024)
The coup that ousted President João Goulart in 1964 had broad support from the Brazilian press. Even after the consolidation of the dictatorship, many media outlets worked to legitimize the regime, although at certain moments these same outlets opposed practices of the military governments that directly affected them, such as censorship of some media vehicles. However, not all media consented to the dictatorship. Journalists engaged in the fight against authoritarianism, and who had connections with revolutionary left-wing organizations, created an alternative press to the complacency of the hegemonic media. Thus, a space of resistance against the generals' regime was opened. Henrique de Souza Filho, known as Henfil, was one of these journalists who fought against the policies of the military presidents. His cartoons, published in the magazine Fradim, were a means used by the cartoonist to denounce the violence of the dictatorial government and the conservatism of part of Brazilian society through humor. These cartoons can be interpreted as historical sources representative of this context and of the conflicts involving groups that fought against the order imposed by the barracks. Understanding the representations of political humor in Henfil's work as a form of contestation against the order established from 1964 and the conservative moralism of a portion of the Brazilian population is the objective of this study. Furthermore, considering that one of the purposes of this research is to provide support to history teachers in their classes, the result of the work was the production of educational material containing texts and proposed activities based on the analysis of comic strips found in Henfil's magazine.
Keywords: Ditadura militar; imprensa alternativa; história em quadrinhos; Henfil; ensino de História; Military dictatorship; alternative press; comics; Henfil; history teaching; CNPQ::CIENCIAS HUMANAS::HISTORIA